Integration of the planning, global localization and path execution in autonomous cars - Ferreira, Ivan dos Santos (2015)
Atlascar is a project developed in the Automation and Robotics laboratory at the Mechanical Department of the University of Aveiro, Portugal. It is used for research in autonomous navigation and for advanced driver assistance systems. The aim of this thesis is to develop a navigation system for path planning, which includes a graphical interface that allows the user to input a nal destination, with possible via points if needed. The application should be able to track the vehicle in real-time and output sequences of high level maneuvers along the mission. New hardware is also to be installed and con gured, namely a new server and a new GPS receiver, which requires an intervention on the previous setup of the Atlascar. The whole system is divided into three parts: Planner, Navigator and User interface. The planner module will be responsible for calculating the path and the instructions. The navigator module will be responsible for processing the data from the planner module ; communicating with a database, read and write values and acquiring data from the GPS. The user interface allows the user to input the desired destination by clicking on a map, this module also allows the user to: monitor the current location of the vehicle; view the path to the destination and it shows the instruction that needs to be done. This module also establishes a communication with the database. This module is optional because the system also works without a user interface, it simply allows the user to do it interactively and it allows motorization. If a wrong decision is made and the user follows a wrong path, the system will recalculate the mission and show a new path.